2021
DOI: 10.2352/issn.2470-1173.2021.5.maap-132
|View full text |Cite
|
Sign up to set email alerts
|

Next Best Light Position: A self configuring approach for the Reflectance Transformation Imaging acquisition process

Abstract: Fast track article for IS&T International Symposium on Electronic Imaging 2021: Material Appearance 2021 proceedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The human–machine interface of LightBot is simple and completely built over a HTTP webserver. Hence, with the API of the LightBot, which gives access to various functionalities of the system, it is convenient to develop new methods in RTI acquisition, such as NBLP [ 15 ], HD-RTI [ 22 ], data stitching, etc. The key benefits of this system design are demonstrated in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human–machine interface of LightBot is simple and completely built over a HTTP webserver. Hence, with the API of the LightBot, which gives access to various functionalities of the system, it is convenient to develop new methods in RTI acquisition, such as NBLP [ 15 ], HD-RTI [ 22 ], data stitching, etc. The key benefits of this system design are demonstrated in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…LightBot accepts the standard Light Positions (.lp) file containing a predefined set of light directions and executes the acquisition by moving the light source oriented in the given directions. Moreover, the system, when combined with the Next Best Light Position [ 15 ], can be used as a standalone unit to perform fully automated RTI acquisition adjustable to the complexity of the object’s surface geometry. Solving the inverse kinematics problem of the system and collision avoidance are key to trajectory planning while executing the acquisition.…”
Section: Proposed Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of this technique is illustrated in Figure 1, where PTM, HSH, and DMD are RTI reconstruction models and stand for Polynomial Texture Mappings, Hemispherical Harmonics, and Discrete Modal Decomposition, respectively. Many new RTI acquisition modalities have recently been developed, including multispectral approaches [34,35], approaches to measure the complete luminance dynamic (HD-RTI, [36][37][38]) self-adaptive approaches to determine the relevant lighting directions (NBLP-RTI, [39]), and even robot-based RTI systems [40]. Within the framework of this research, we focus on the RTI acquisition parameters associated with the conventional approach.…”
Section: Reflectance Transformation Imagingmentioning
confidence: 99%
“…Some images are more important than others. It is also observed that some regions in the hemisphere need more dense acquisition than others because reflectance is changing drastically in these regions [14].…”
mentioning
confidence: 99%